2008
DOI: 10.1890/070126
|View full text |Cite
|
Sign up to set email alerts
|

Silica: an essential nutrient in wetland biogeochemistry

Abstract: Recent research has emphasized the importance of terrestrial ecosystems in the global biogeochemical cycle of silica (Si). The production, retention, and dissolution of amorphous silica of biological origin in soils and vegetation effectively control terrestrial Si fluxes. However, surprisingly little is known about the role of wetlands in these processes. Wetlands are known hotspots for both nitrogen and phosphorus cycling, and there have been countless studies and numerous reviews on these nutrients worldwid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(125 citation statements)
references
References 46 publications
4
120
1
Order By: Relevance
“…624 E. Struyf et al: Silica storage in a riparian wetland for exported DSi (Bartoli, 1983;Farmer et al, 2005). More recently, a literature overview suggested that wetlands have the potential to exhibit a profound influence on terrestrial silica transport and storage (Struyf and Conley, 2009). Wetlands can modify nutrient fluxes along the aquatic continuum through transformation and storage.…”
Section: Introductionmentioning
confidence: 99%
“…624 E. Struyf et al: Silica storage in a riparian wetland for exported DSi (Bartoli, 1983;Farmer et al, 2005). More recently, a literature overview suggested that wetlands have the potential to exhibit a profound influence on terrestrial silica transport and storage (Struyf and Conley, 2009). Wetlands can modify nutrient fluxes along the aquatic continuum through transformation and storage.…”
Section: Introductionmentioning
confidence: 99%
“…4b). Diatom productivity and abundance are often estimated from biogenic silica (BSi; Conley and Schelske 2001;Struyf and Conley 2009), and these concentrations are low throughout the zone (1.8-2.9 wt%; Fig. 5).…”
Section: Daz1 (1900-1978)mentioning
confidence: 99%
“…Moreover, grasses and sedges are known to contain significant amount of amorphous silica in their biomass (Saccone et al, 2007). In a recent study, Struyf and Conley (2009) have shown that especially these arctic wetlands are impressive storages of amorphous silica (ASi) that are either diatom frustules or phytoliths (Piperno, 1988). Initial analyses show that subarctic wetlands in Northern Sweden contain 1-5% of ASi by weight percent, which is an order of magnitude above the amount stored in temperate wetlands and confirm the capacity of subarctic wetlands to accumulate large amounts of ASi.…”
Section: The Riparian Zone -A Hot Spot For Dsi River Loading In Arctimentioning
confidence: 99%
“…Thus, the soil/water contact time will obviously increase downstream. A long soil/water contact time increases also the potential for a build up of a ASi pool in the soils that is further enhanced by regular flooding events that in turn lead to an enhanced deposition of suspended soils, sediment associated phytoliths and diatoms (Struyf and Conley, 2009). In other words, these authors suggest that the wetland rich areas, such as the riparian zone, of arctic and boreal river systems has evolved to a massive Si storage since the last glaciation and act now as a significant source for DSi in these river systems.…”
Section: Dem Indicating Flow Path and Soil Contact Times Of Waters Inmentioning
confidence: 99%
See 1 more Smart Citation